The Influence Of Capabilities And Digital Marketing On The Success Of Online MSME Businesses In Bengkulu City - Mei Sela Pirdayanti; Ahmad Soleh; Nirta Vera Yustanti (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study aims to examine the influence of capabilities and digital marketing on the success of online MSME businesses in Bengkulu City. The research uses a quantitative associative method with a sample of 60 MSME respondents who have implemented digital marketing strategies. Data were collected through structured questionnaires and analyzed using multiple linear regression with SPSS to test the research hypotheses. Research Results The results indicate that capabilities and digital marketing have a positive and significant effect on the success of online MSME businesses, both partially and simultaneously. The regression coefficients for capabilities and digital marketing were 0.347 and 0.547 respectively, with significance values below 0.05. Together, these variables explain about 60.4% of the variance in online business success. Strengthening internal capabilities and effective digital marketing strategies are crucial to achieving sustainable business success.